2002
DOI: 10.5194/npg-9-419-2002
|View full text |Cite
|
Sign up to set email alerts
|

Fractal time statistics of AE-index burst waiting times: evidence of metastability

Abstract: Abstract. Recent observations and analyses evidenced that the magnetotail, as well as the magnetospheric dynamics are characterised by a scale-free behaviour and intermittence. These results, along with numerical simulations on cellular automata, suggest that the observed scale-invariance may be due to forced and/or self-organised criticality (FSOC), meaning that the magnetotail operates near a marginally stable state (Chang, 1999). On the other hand, it was underlined that a complex magnetic field topology in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 26 publications
(34 reference statements)
3
12
0
Order By: Relevance
“…For instance, Balasis et al (2006) have shown the occurrence of an interesting transition from the anti-persistent to the persistent character in the fluctuations of Dst index, which closely corresponds to a transition from a regime of quiet to one of high magnetospheric activity, characterized by the occurrence of intense geomagnetic storms. A similar behavior has been also documented in the case of the auroral electrojet (AE) index (e.g., Uritsky and Pudovkin,and discussed in a more general scenario, involving a near forced and/or self-organized criticality (FSOC) dynamics (Consolini, 1997;Uritsky and Pudovkin, 1998;Chang, 1999;Chang et al, 2003;Consolini and Chang, 2001;Consolini and De Michelis, 2002;Wanliss and Weygand, 2007;Wanliss and Uritsky, 2010).…”
Section: Introductionmentioning
confidence: 82%
“…For instance, Balasis et al (2006) have shown the occurrence of an interesting transition from the anti-persistent to the persistent character in the fluctuations of Dst index, which closely corresponds to a transition from a regime of quiet to one of high magnetospheric activity, characterized by the occurrence of intense geomagnetic storms. A similar behavior has been also documented in the case of the auroral electrojet (AE) index (e.g., Uritsky and Pudovkin,and discussed in a more general scenario, involving a near forced and/or self-organized criticality (FSOC) dynamics (Consolini, 1997;Uritsky and Pudovkin, 1998;Chang, 1999;Chang et al, 2003;Consolini and Chang, 2001;Consolini and De Michelis, 2002;Wanliss and Weygand, 2007;Wanliss and Uritsky, 2010).…”
Section: Introductionmentioning
confidence: 82%
“…Intuitively an intermittent signal will exhibit peaks spaced apart by long distances/intervals. The study of the distribution of the waiting time or burst time has for example gained much attention in research about the solar wind-magnetosphere-ionosphere system [e.g., Freeman et al, 2000;Lui et al, 2000;Chapman and Watkins, 2001;Consolini and De Michelis, 2002] in relation to Self-Organized Criticality (SOC) states, which can naturally drive a system "scale free" (self-similar), the latter being a characteristic of turbulence [Bak et al, 1987]. The study of SOC systems is outside of the scope of this paper, and we only mention here that the duration of events in a scale-invariant processes are expected to follow a power law [e.g., Bak et al, 1987;Chang, 1992].…”
Section: Waiting Time Statisticsmentioning
confidence: 99%
“…In this framework, magnetic substorms are better described in terms of noise-induced topological transitions in an extended out-of-equilibrium system. In other words, the magnetic substorm is the set of phenomena during which a reduction in topological complexity takes place (Chang, 2001a(Chang, , 2001bChang, 2001, 2002;Consolini and De Michelis, 2002). The role of the solar wind driver would be to enhance the internal noise (i.e.…”
Section: On the Transition From The Anti-persistent To Persistent Regimementioning
confidence: 99%